Lost or saved? The future of work in the face of the fourth Industrial Revolution - Rubbi, Lautaro N. (2020)
This narrative bibliographical analysis aims to inquire into how many jobs will be lost or gained in the mediumterm future as a result of the automation of labor being introduced as part of the fourth Industrial Revolution. The main focus is upon academic texts, coupled with analysis of the public policies of different countries around the world and the business documents of multinational companies, which address different time and spatial frameworks in their predictions. There exists a wide variety of conclusions among different authors, with no consensus on whether there will be an overall gain or loss of jobs in absolute terms; however, we identify three basic consensuses: 1) The most vulnerable countries and sectors are those that depend upon repetitive rather than creative jobs. Emerging or developing countries will be fundamentally affected; 2) A high degree of social fragmentation is expected, with a concentration of jobs at both extremes of the salary and cognitive demands scales; and, 3) More than ever before, education will be the key factor in the raising of living standards, at both individual and societal levels.